The Sensorial and Legislative Role in Fighting (both) Administrative Financial Corruption (مجلة المنصور, 2022)
Corruption is a phenomenon that leads to discontent on the part of people. The spread of corruption often ends in a failed state and the moral decline of society. Legislations and religions stipulate that corruption and those who are corrupted must be registered vehemently. They also warn them that they will be this disgraced and punished. Corruption often has political and social aims.Therefore, efforts have to be made to get rid of it. Bothe judicial and censorial roles have to be activated for this purpose. I have divided my paper into an introduction including a list containing recommendations, two sections and several demands. The first section deals with religious , social and media aspects , the second with judicial , legislative and penal ones .